Galaxy Zoo: the interplay of quenching mechanisms in the group environment - Smethurst, Rebecca J.; Lintott, C.J.; Bamford, S.P.; Hart, R.E.; Kruk, S.J.; Masters, K.L.; Nichol, R.C.; Simmons, B.D. (Oxford University Press, 2017)
Does the environment of a galaxy directly influence the quenching history of a galaxy? Here, we investigate the detailed morphological structures and star formation histories of a sample of SDSS group galaxies with both classifications from Galaxy Zoo 2 and near ultra-violet (NUV) detections in GALEX. We use the optical and NUV colours to infer the quenching time and rate describing a simple exponentially declining star formation history for each galaxy, along with a control sample of field galaxies. We find that the time since quenching and the rate of quenching do not correlate with the relative velocity of a satellite but are correlated with the group potential. This quenching occurs within an average quenching time-scale of ∼2.5 Gyr from star forming to complete quiescence, during an average infall time (from ∼10 R200 to 0.01 R200) of ∼2.6 Gyr. Our results suggest that the environment does play a direct role in galaxy quenching through quenching mechanisms that are correlated with the group potential, such as harassment, interactions or starvation. Environmental quenching mechanisms that are correlated with satellite velocity, such as ram-pressure stripping, are not the main cause of quenching in the group environment. We find that no single mechanism dominates over another, except in the most extreme environments or masses. Instead, an interplay of mergers, mass and morphological quenching and environment-driven quenching mechanisms dependent on the group potential drive galaxy evolution in groups.